Spearheading Development Culture - A Case Study - Mukherjee, Arunava Narayan (Prabandhan: Indian Journal of Management, 2010)
The case study is about transforming the organizational culture of Green Field Group of Companies- an agro based business group. Within a small span of time, with the application of technology and scientific methods of land reclamation and use of appropriate agro-forestry cropping schedule, Green Field became quite a successful business venture. Although the founder and promoters of the business duly emphasized on technology related business processes, they overlooked the human organization of business, especially the majority of work force who belonged to the tribal community. Consequently, despite having achieved great success at the initial stage with the help of technology and the allied process, in the long run, the organization failed to deliver. Therefore, attempts were made to address the issues concerning the human resource of the organization. In this process, it was found there was an urgent need for change of human climate to usher in organizational development. With sincere Human Resource Development efforts, a climate of trust and faith could be developed. A sense of harmony prevailed among the work force irrespective of their background and position in the organisation. While undertaking this process, the organization of Green Field learnt to adopt new vision and corporate philosophy. Accordingly there was institutionalisation of people oriented practices which ultimately led to the growth of the organization.